Decreased modulation by the risk level on the brain activation during decision making in adolescents with internet gaming disorder - Qi, Xin; Du, Xin; Yang, Yongxin; Du, Guijin; Gao, Peihong; Zhang, Yang; Qin, Wen; Li, Xiaodong; Zhang, Quan (Frontiers in Behavioral Neuroscience, 2015)
Greater impulse and risk-taking and reduced decision-making ability were reported as the main behavioral impairments in individuals with Internet gaming disorder (IGD), which has become a serious mental health issue worldwide. However, it is not clear to date how the risk level modulates brain activity during the decision-making process in IGD individuals. In this study, 23 adolescents with IGD and 24 healthy controls (HCs) without IGD were recruited, and the Balloon Analog Risk Task (BART) was used in a functional magnetic resonance imaging (fMRI) experiment to evaluate the modulation of the risk level (the probability of balloon explosion) on brain activity during risky decisionmaking in IGD adolescents. Reduced modulation of the risk level on the activation of the right dorsolateral prefrontal cortex (DLPFC) during the active BART was found in IGD group compared to the HCs. In the IGD group, there was a significant negative correlation between the risk-related DLPFC activation during the active BART and the Barratt impulsivity scale (BIS-11) scores, which were significantly higher in IGD group compared with the HCs. Our study demonstrated that, as a critical decision-making-related brain region, the right DLPFC is less sensitive to risk in IGD adolescents compared with the HCs, which may contribute to the higher impulsivity level in IGD adolescents.